α(4)β(7) independent pathway for CD8(+) T cell–mediated intestinal immunity to rotavirus - Kuklin, Nelly A. (American Society for Clinical Investigation, 2000)
Rotavirus (RV), which replicates exclusively in cells of the small intestine, is the most important cause of severe diarrhea in young children worldwide. Using a mouse model, we show that expression of the intestinal homing integrin α(4)β(7) is not essential for CD8(+) T cells to migrate to the intestine or provide immunity to RV. Mice deficient in β7 expression (β7(–/–)) and unable to express α(4)β(7) integrin were found to clear RV as quickly as wild-type (wt) animals. Depletion of CD8(+) T cells in β7(–/–) animals prolonged viral shedding, and transfer of immune β7(–/–) CD8(+) T cells into chronically infected Rag-2–deficient mice resolved RV infection as efficiently as wt CD8(+) T cells. Paradoxically, α(4)β(7)(hi) memory CD8(+) T cells purified from wt mice that had been orally immunized cleared RV more efficiently than α(4)β(7)(low) CD8(+) T cells. We explained this apparent contradiction by demonstrating that expression of α(4)β(7) on effector CD8(+) T cells depends upon the site of initial antigen exposure: oral immunization generates RV-specific CD8(+) T cells primarily of an α(4)β(7)(hi) phenotype, but subcutaneous immunization yields both α(4)β(7)(hi) and α(4)β(7)(low) immune CD8(+) T cells with anti-RV effector capabilities. Thus, α(4)β(7) facilitates normal intestinal immune trafficking to the gut, but it is not required for effective CD8(+) T cell immunity.